Homonimy urbanonimiczne w rosyjskim języku mówionym - Щербак, Антонина (Studia Rossica Posnaniensia, 2018)
The idea of the Polish scientist, Jerzy Kaliszan, regarding the omo-reference of the facts of word-formation and form-formation in the Russian language is developing on the basis of Russian urbanonyms; it has been established that the formation of targeted linear inner city objects determines the internal dynamism of the grammatical system of the language, expands the fund of verbal resources, increasing the nomination possibilities and expanding the national linguistic picture of the world.